Evaluation of Municipal Water Distribution System Reliability Using Minimum Cut-set Method - Muhammad A. Al-Zahrani; Juned Laiq Syed (Journal of King Saud University: Engineering Sciences)
Reliability analysis of water distribution systems is a complex task, as it requires both definition and calculation of reliability measures. In this paper, a methodology for evaluating water distribution system reliability is developed and demonstrated on a real water distribution network. The methodology comprises of two steps: (1) nodal pressures are calculated using hydraulic simulation program (EPANET), and (2) the minimum cut-set method is applied to calculate nodal and system reliabilities of AI-Khobar water distribution network. The results show that the hydraulic reliability of the central part of AI-Khobar water distribution system is 69.73%.